Chen-Ricci Inequalities with a Quarter Symmetric Connection in Generalized Space Forms - Ali H. Al-Khaldi; Mohd. Aquib; Mohd Aslam; Meraj Ali Khan (Advances in Mathematical Physics)
In this article, we obtain improved Chen-Ricci inequalities for submanifolds of generalized space forms with quarter-symmetric metric connection, with the help of which we completely characterized the Lagrangian submanifold in generalized complex space form and a Legendrian submanifold in a generalized Sasakian space form. We also discuss some geometric applications of the obtained results.